Optimization and mechanism of acoustic absorption of Alberich coatings on a steel plate in water. (November 2018) - Zhao, Dan; Zhao, Honggang; Yang, Haibin; Wen, Jihong
Abstract: The acoustic absorption of Alberich coatings is generally a topic attracting persistent interests. The present paper optimizes acoustic absorption of two types of Alberich coatings on a steel plate immersed in water using a differential evolution algorithm combined with a finite element method. Both the coatings contain cylindrical cavities of mixed sizes. We compare the optimized absorption for different arrangement, i.e., the both coatings on different surfaces or only on the outer surface of the steel plate. The results show that the different coatings on both surfaces of the steel plate can achieve better sound absorption from 1.3 kHz to 10.0 kHz. The power dissipation density and the displacement pattern are used to analyze the broadband absorption mechanism induced by the acoustic resonance and the acoustic coupling between the optimized coatings. The results validate the idea that it can effectively enhance the low-frequency and bandwidth of the absorption by laying different coatings on both surfaces of the steel plate.